Prospek Pengembangan UMKM Beras Organik dalam Mendukung Konsumsi Pangan Sehat dan Agribisnis Berkelanjutan di Indonesia - Roosganda Elizabeth (Universitas Galuh, 2026)
The increasing public awareness of healthy lifestyles, food safety, and environmental sustainability has created significant opportunities for the development of organic rice businesses in Indonesia. Organic rice is increasingly recognized as a healthy food product that offers added value compared to conventionally produced rice. In this context, Small and Medium Enterprises (SMEs) play a strategic role in strengthening the organic rice value chain through processing, packaging, marketing, and distribution activities. This study aims to examine the prospects for developing organic rice SMEs in supporting healthy food consumption and sustainable agribusiness in Indonesia. The study employed a literature review approach by analyzing various scientific publications, government reports, and relevant secondary data related to organic agriculture, SMEs, healthy food consumption, and sustainable agribusiness. The results indicate that the development of organic rice SMEs is supported by increasing consumer demand for healthy food products, growing market opportunities, and rising awareness of environmental sustainability. However, several challenges remain, including high certification costs, limited access to financing, inadequate market networks, low consumer literacy, and constraints in maintaining a consistent supply of organic rice. Therefore, strengthening institutional capacity, expanding market access, improving digital marketing capabilities, facilitating organic certification, and enhancing stakeholder collaboration are essential strategies for supporting the sustainable development of organic rice SMEs. The study concludes that organic rice SMEs have substantial potential to contribute to healthy food systems, increase farmers’ and entrepreneurs’ incomes, and promote sustainable agribusiness development in Indonesia.